Reflectivity of VUV-sensitive silicon photomultipliers in liquid Xenon. (2nd August 2021) - Wagenpfeil, M.; Ziegler, T.; Schneider, J.; Fieguth, A.; Murra, M.; Schulte, D.; Althueser, L.; Huhmann, C.; Weinheimer, C.; Michel, T.; Anton, G.; Adhikari, G.; et al.
Abstract: Silicon photomultipliers are regarded as a very promising technology for next-generation, cutting-edge detectors for low-background experiments in particle physics. This work presents systematic reflectivity studies of Silicon Photomultipliers (SiPM) and other samples in liquid xenon at vacuum ultraviolet (VUV) wavelengths. A dedicated setup at the University of Münster has been used that allows to acquire angle-resolved reflection measurements of various samples immersed in liquid xenon with 0.45° angular resolution. Four samples are investigated in this work: one Hamamatsu VUV4 SiPM, one FBK VUV-HD SiPM, one FBK wafer sample and one Large-Area Avalanche Photodiode (LA-APD) from EXO-200. The reflectivity is determined to be 25–36 % at an angle of incidence of 20° for the four samples and increases to up to 65 % at 70° for the LA-APD and the FBK samples. The Hamamatsu VUV4 SiPM shows a decline with increasing angle of incidence. The reflectivity results will be incorporated in upcoming light response simulations of the nEXO detector.